Perioperative nutritional risk and its influencing factors in patients with oral cancer: a longitudinal study - Wang, Guifen; Ou, Meijun; Chen, Hong; Zhu, Shujuan; Chen, Yongyi; Xu, Xianghua (Frontiers in Nutrition, 2023)
Introduction: We aimed to investigate the nutritional risk status and dynamic changes in patients with perioperative oral cancer at different stages and analyze the factors influencing nutritional risk and the correlation among body mass index, nutrition-related symptoms, and nutritional risk. Methods: In total, 198 patients with oral cancer who were hospitalized in the Head & Neck Surgery Departments of a tertiary cancer hospital in Hunan Province, China, from May 2020 to January 2021, were selected as participants. The Nutritional Risk Screening 2002 scale and Head and Neck Patient Symptom Checklist were used to assess patients on admission day, 7 days post-surgery, and 1 month post-discharge. Multivariate analysis of variance, paired t-test, and generalized estimating equation were used to analyze the trajectory and influencing factors of nutritional risk in patients with perioperative oral cancer. Spearman’s correlation analysis was used to explore the correlation among body mass index, symptoms, and nutritional risk. Results: The nutritional risk scores of patients with oral cancer at the three time points were 2.30±0.84, 3.21±0.94, and 2.11±0.84, respectively, and the differences were significant (P<0.05). The incidences of nutritional risk were 30.3%, 52.5%, and 37.9%, respectively. The factors influencing nutritional risk included education level, smoking status, clinical stage, flap repair, and tracheotomy (β=-0.326, 0.386, 0.387, 0.336, and 0.240, respectively, P<0.05). Nutritional risk was negatively correlated with body mass index (rs=-0.455, P<0.01) and positively correlated with pain, loss of appetite, sore mouth, bothersome smells, swallowing difficulty, taste changes, depression, chewing difficulty, thick saliva, and anxiety (rs=0.252, 0.179, 0.269, 0.155, 0.252, 0.212, 0.244, 0.384, 0.260, and 0.157, respectively, P<0.05). Conclusions: The incidence of nutritional risk in patients with perioperative oral cancer was high, and the trajectory of nutritional risk changed over time. Strengthening the nutritional monitoring and management of postoperative patients or those with low education level, advanced-stage cancer, flap repair, tracheotomy, and low body mass index; strengthening tobacco control management; and controlling nutrition-related discomfort symptoms in perioperative oral cancer patients are necessary.